Mathematical Model of the Information Factor of the Evolution of the Lemaitre–Friedmann Primordial Atoms in Superspace-Time; Russian Physics Journal; Vol. 58, № 9 - Lasukov V. V. Vladimir Vasilievich; Rozhkova S. V. Svetlana Vladimirovna; Abdrashitova M. O. Mariya Ovseevna; Ilkin E. E. Egor Evgenjevich; Novoselov V. V. Vyacheslav Vladimirovich (2016, 2016)
Title screen